Traveling different : vacation strategies for parents of the anxious, the inflexible, and the neurodiverse - Barclay, Dawn M., 1959- (Rowman & Littlefield, 2022)
"Every family deserves to travel, and the purpose of this book is to offer tips that open the world to every parent and child, no matter what their challenges"--